Cálculo de tensão induzida por descarga atmosférica em linhas aéreas polifásicas e multiaterradas: implementação no PSCAD®/EMTDCtm - Sandro de Castro Assis (2006)
This work presents the implementation of lightning induced voltage calculation in multiphase overhead lines. The implementation is done using a electromagnetic transient calculation program as a dedicated component. The implemented methodology is based on the theory proposed by Sune Rusck in 1957 and adapted by Ivan Lopes in 1990. Ruscks theory, which provides an equation for the lightning induced voltage in infinite overhead lines without discontinuities over a perfect ground, is modified to take into account finite lines with multiple grounding. The implemented component extends the methodology to multiphase overhead lines with multiple grounding. Theoretical cases are analyzed clarifying the influence of lightning parameters and grounding configuration in induced voltages in multiphase lines. The results are compared to those from other authors validating the implementation.